Recovery from work: Improving recovery through acceptance and commitment training - Honkasalo, Elina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2025)
My thesis aimed to examine effective recovery interventions. I was particularly interested in investigating whether Acceptance and Commitment Training (ACT)-based methods could promote recovery from work. Another important focus of my thesis was to examine how recovery interventions produce their effects, which has so far received less research attention. This thesis also sought to provide better insight into previous worksite ACT and recovery intervention studies. The main theoretical frameworks my thesis utilised were the recovery experiences framework (Sonnentag & Fritz, 2007), the ACT model (S. C. Hayes et al., 1999), and resource-based theories, including the Conservation of Resources Theory (COR) of burnout and work-engagement (Gorgievski & Hobfoll, 2008), and Goal-related Context-sensitivity hypothesis (F. W. Bond et al., 2006). My thesis approached psychological flexibility (a core concept of ACT) through these resource theories in particular. My thesis consists of three essays: a narrative literature review of prior recovery interventions, a systematic literature review of previous worksite ACT studies, and an intervention study with a waitlist control group. The narrative review comprised 15 studies, while the systematic review critically examined 29 articles. In the intervention study, 59 participants from two Finnish public sector organisations were assigned to an immediate ACT group (n = 32) or a waitlist control group (n = 27). The groups received 12 hours of training, and the intervention imparted a mixture of recovery-, mindfulness- and values-based skills. Data were collected at the baseline (T1), at the end of the immediate ACT group’s training (T2), and at the end of the waitlist control group’s training (T3). The findings from the narrative review suggest that recovery-specific training interventions and interventions not specifically tailored for recovery (e.g., mindfulness) can deliberately improve recovery. The findings likewise indicate that improved cognition and emotion regulation may be the mechanisms by which these interventions work. In turn, results from the systematic review demonstrate that worksite ACT interventions effectively improve employee mental health and well-being. Similarly, worksite ACT interventions were found to increase positive work-related outcomes (e.g., work productivity and personal accomplishment) and decrease negative outcomes (e.g., stress and burnout). Consistent with the ACT model, the review findings also revealed that ACT processes are likely to explain these intervention effects. Finally, the results of the intervention study show that ACT-based recovery intervention can increase recovery experiences and psychological flexibility and decrease the need for recovery. The findings further indicate that the observed effects occurred through improvements in recovery experiences, as proposed by the theoretical frameworks applied to the recovery process, while no such mediation effect was detected for psychological flexibility. Taken together, the findings of my thesis support the view that recovery is a malleable process and suggest that efficient cognition and emotion regulation may play a crucial role in recovery promotion. This thesis also presents the first empirical evidence that integrating recovery intervention with ACT methods can benefit recovery, although recovery promotion seemingly occurs through recovery and not ACT processes. Finally, this thesis presents that ACT is useful for recovery and effectively enhances employee mental health, well-being, and work-related outcomes; thus, it is worth applying more widely in the workplace.